Beyond Hindu?Muslim unity: Gandhi, the Parsis and the Prince of Wales Riots of 1921 - Patel, Dinyar (2018)
Between 17 and 20 November 1921, Bombay was convulsed by the Prince of Wales Riots, which coincided with the arrival of the future King Edward VIII in the city. The riots constituted an extremely important moment in the Non-Cooperation Movement, the political transformation of Bombay and the development of M.K. Gandhi?s political thought. Additionally, the riots upturned familiar notions of communalism: angry at repeated violations of a hartal Gandhi declared for the day of the Prince?s arrival, Muslim and Hindu supporters of the Non-Cooperation and Khilafat movements joined together to attack supposedly loyalist minorities, especially Parsis. Herein lay the riots? broader significance. During the Non-Cooperation Movement, Gandhi had been keen to recruit the active support of the Parsi community. He was well aware of their financial and political clout and their leadership roles in liberal nationalist circles. Most Parsis, however, expressed strong reservations about Gandhi?s tactics, believing that a mass political movement under the banner of ?Hindu?Muslim unity? would be injurious to smaller minority communities. The riots, therefore, confirmed Parsis? worst fears about Gandhi?s politics and their majoritarian implications. Gandhi, for his part, worked tirelessly to repair his relationships with the Parsis and reassure them of the Congress? commitments towards minority rights. He reconsidered how smaller communities fit into India?s communal dynamics. By December 1921, Gandhi even unfurled a new slogan that was used towards the end of the Non-Cooperation Movement: ?Hindu?Muslim?Sikh?Parsi?Christian?Jew unity?.
Keywords: Parsis; Bombay riots; Gandhi, M.K.; Riots - India; Communalism - India; Communalism